Yield of exome sequencing in patients with developmental and epileptic encephalopathies and inconclusive targeted gene panel - Sedlackova, Lucie; Sterbova, Katalin; Vlckova, Marketa; Seeman, Pavel; Zarubova, Jana; Marusic, Petr; Krsek, Pavel; Krijtova, Hana; Musilova, Alena; Lassuthova, Petra (European journal of paediatric neurology, 2024)
OBJECTIVE: Developmental and epileptic encephalopathies (DEEs) are a group of severe, early-onset epilepsies characterised by refractory seizures, developmental delay, or regression and generally poor prognosis. DEE are now known to have an identifiable molecular genetic basis and are usually examined using a gene panel. However, for many patients, the genetic cause has still not been identified. The aims of this study were to identify causal variants for DEE in patients for whom the previous examination with a gene panel did not determine their genetic diagnosis. It also aims for a detailed description and broadening of the phenotypic spectrum of several rare DEEs. METHODS: In the last five years (2015-2020), 141 patients from all over the Czech Republic were referred to our department for genetic testing in association with their diagnosis of epilepsy. All patients underwent custom-designed gene panel testing prior to enrolment into the study, and their results were inconclusive. We opted for whole exome sequencing (WES) to identify the cause of their disorder. If a causal or potentially causal variant was identified, we performed a detailed clinical evaluation and phenotype-genotype correlation study to better describe the specific rare subtypes. RESULTS: Explanatory causative variants were detected in 20 patients (14%), likely pathogenic variants that explain the epilepsy in 5 patients (3.5%) and likely pathogenic variants that do not fully explain the epilepsy in 11 patients (7.5%), and variants in candidate genes in 4 patients (3%). Variants were mostly de novo 29/40 (72.5%). SIGNIFICANCE: WES enables us to identify the cause of the disease in additional patients, even after gene panel testing. It is very important to perform a WES in DEE patients as soon as possible, since it will spare the patients and their families many years of a diagnostic odyssey. In particular, patients with rare epilepsies might significantly benefit from this approach, and we propose using WES as a new standard in the diagnosis of DEE instead of targeted gene panel testing.
Keywords: epilepsie; lidé; epilepsie generalizovaná; genetické asociační studie; Phenotype; Epilepsy; fenotyp; Genetic Testing; Humans; Exome Sequencing; genetické testování; sekvenování exomu; Epilepsy, Generalized; Genetic Association Studies